Book-to-market decomposition, net share issuance, and the cross section of global stock returns - Douglas W. Blackburn; Nusret Cakici (Journal of Risk and Financial Management, 2019)
This paper provides global evidence supporting the hypothesis that expected return models are enhanced by the inclusion of variables that describe the evolution of book-to-market-changes in book value, changes in price, and net share issues. This conclusion is supported using data representing North America, Europe, Japan, and Asia. Results are highly consistent across all global regions and hold for small and big market capitalization subsets as well as in different subperiods. Variables measured over the past twelve months are more relevant than variables measured over the past thirty-six months, demonstrating that recent news is more important than old news.
Keywords: F20; F21; F30; G10; G11; G12; G15; 330; global return predictability; cross-section of returns; book-to-market; net share issues